Admissibility and Measurable Utility Functions - Quirk, James P.; Saposnik, Rubin (Review of Economic Studies, 1962)
James P. Quirk, Rubin Saposnik; Admissibility and Measurable Utility Functions*, The Review of Economic Studies, Volume 29, Issue 2, 1 February 1962, Pages